Copper‐Catalyzed Enantioselective Trifluoromethoxylation of Propargyl Sulfonates. (27th March 2023) - Hou, Yangdong; Zhang, Zhang; Sun, Xinyu; Yang, Zheng; Luan, Yu‐Xin; Tang, Pingping
Abstract: Due to the strong electron‐withdrawing nature and high lipophilicity of trifluoromethoxy group (OCF3 ), methods for introducing OCF3 into organic molecules are in high demand. However, the research area of direct enantioselective trifluoromethoxylation is still in the embryonic stage, with limited enantioselectivity and/or reaction types. Here, we describe the first copper‐catalyzed enantioselective trifluoromethoxylation of propargyl sulfonates using trifluoromethyl arylsulfonate (TFMS) as the trifluoromethoxy source in up to 96 % ee. Abstract : Currently, great challenges still remain for direct asymmetric trifluoromethoxylation with only two successful reports since the first discovery. Here, by subtly tuning the leaving group, protecting group, ligand structure, reaction temperature, solvent and base, we finally realized a copper‐catalyzed enantioselective trifluoromethoxylation of propargyl sulfonates for the first time.